2006
DOI: 10.1158/1535-7163.mct-06-0351
|View full text |Cite
|
Sign up to set email alerts
|

Pretherapy nuclear factor-κB status, chemoradiation resistance, and metastatic progression in esophageal carcinoma

Abstract: Background: Transcriptional factor nuclear factor-KB (NF-KB) seems to be associated with aggressive clinical biology (chemoradiation resistance and metastatic progression) of esophageal cancer. We hypothesized that activated NF-KB would define clinical biology irrespective of the type of chemotherapy or sequence administered. Methods: Pretherapy and/or posttherapy cancer specimens were examined for activated NF-KB and correlated with pathologic response to chemoradiation, metastatic potential, overall survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 25 publications
3
57
0
3
Order By: Relevance
“…We also showed that in patients who are undergoing preoperative chemoradiation, nuclear NF-nB was independently associated with poor disease-free survival (DFS) or overall survival (OS; refs. 28,29). In our studies, we observed two distinct NF-nB patterns whereas some E/GEJ cancers presented intrinsic (i.e., pretreatment) NF-nB activation, whereas in others the activation seemed to follow the exposure to chemoradiation treatment.…”
Section: Introductionsupporting
confidence: 46%
“…We also showed that in patients who are undergoing preoperative chemoradiation, nuclear NF-nB was independently associated with poor disease-free survival (DFS) or overall survival (OS; refs. 28,29). In our studies, we observed two distinct NF-nB patterns whereas some E/GEJ cancers presented intrinsic (i.e., pretreatment) NF-nB activation, whereas in others the activation seemed to follow the exposure to chemoradiation treatment.…”
Section: Introductionsupporting
confidence: 46%
“…However, nonsteroidal antiinflammatory drugs are not specific and usually have side effects that prevent their long-term administration. Advances in preclinical research have highlighted the fact that resistance to chemotherapy as well as radiotherapy are caused by the chronic activation of NF-B (24 ). Several inhibitors of NF-B or STAT3 have been reported to enhance the effect of therapeutic agents in the treatment of bone metastasis in prostate cancer.…”
Section: Tumor Microenvironment and Cancer Therapymentioning
confidence: 99%
“…Using the Spitzer index, there was no difference in global quality of life however, a significantly greater decrease in quality of life was observed in the surgery arm during the postoperative period (7.52 vs. 8.45, p<0.01, respectively) [65]. A separate analysis revealed that compared with split course radiation, patients who received standard course radiation had improved 2-year local relapse free survival rates (77% vs. 57%, p=0.002) but no significant difference in overall survival (37% vs. 31%) [66].…”
Section: Is Surgery Necessary Following Chemoradiation?mentioning
confidence: 90%